EP1071 Genotype distribution of HPV in patients with histologically proven findings for cervical intraepithelial neoplasia or invasive cervical cancer in Macedonia. (1st November 2019) - Dimitrov, G; Dzikova, E; Dimitrov, G; Tofoski, G; Daneva Markova, A; Joksimovik, M; Kjajova, I
Abstract : Introduction/Background: The aim of this study was to provide basic data on genotype distribution of HPV in patients from Macedonia with histologically proven findings for squamous intraepithelial lesions or invasive cervical cancer, in order to better plan the vaccination program and screening for cervical cancer and to plan and with hope to introduce a National cervical cancer screening programme with HPV genotyping as a primary screening test. Methodology: We analyzed the histological findings positive for cervical intraepithelial neoplasia or invasive cervical cancer and genotype HPV distribution results in 564 patients treated at the University Clinic for Gynecology and Obstetrics in Skopje, Macedonia, during 2017. Results: 78% of the total of 564 subjects appeared to be positive for HPV. The genotype distribution of HPV in cervical squamous intraepithelial lesions or invasive squamous cell cancer and adenocarcinoma of the uterine cervix was 69.2%, 87.2%, 97.6% and 71.4%, respectively. The distribution of HR HPV types was for 21% higher in HSIL lesions than in LSIL. The most frequent isolated HPV types were: 16, 18, 35, 31, 33, 58, 6, 11 and 40. The most common genotype was HPV 16 with the highest rate in HSIL (48.4%), a little bit lower in invasive squamous cancer (30.1%) and the lowest in LSIL (19.6%). On the other hand, the prevalence of HPV 18 was the highest in patients with invasive adenocarcinoma of the uterine cervix, 30.1%. Conclusion: In Macedonia, the most predominant genotypes of HPV in squamous intraepithelial lesions and invasive cervical cancers are the human papillomavirus types 16, 18, 35, 31, 33, 58, 6, 11 and 40 which is very important to know in order to plan the vaccination program and to create an expedient National cancer screening programme that will be more effective strategy against invasive cervical cancer. Disclosure: Nothing to disclose